Soconusco, an Affluent Production Zone in the Mesoamerican World System - Navarro Castillo, Marx (2023)
The Soconusco region in the state of Chiapas, Mexico, has been the research object of archaeological specialists since the 19th century. Several investigations have been conducted in the region; the one presented here focuses on the Classic period, particularly concerning the role it may have played in what some authors have called the Mesoamerican World System. Based on the study of the ceramic type known as plumbate, which has been identified in places as far away as Nayarit (western Mexico) to Costa Rica and from Monte Albán to Tula, we are in a position to point to the existence of well-established interaction networks that allowed the mobilization of this ware. The area studied by the Soconusco Coast Archaeological Project (PACS) identified the places of production of plumbate ceramics and thus hierarchical and trade relationships have been proposed not only at a local or regional level, but also at a Pan-Mesoamerican scale.Such interactions can be understood in terms of the World System, which, although originally conceived to understand current economic processes, can undoubtedly be applied to understand ancient societies. This approach highlights the very essence of archaeology that due to the recentness of the discipline tends to use terms created in other areas of research, representing undoubtedly its multidisciplinary character. Therefore, the proposal of this article is that the Soconusco was a zone of affluent production since the Classic period, considering the distribution of Plumbate ceramics throughout Mesoamerica as the main source.